Changing governance and management in higher education the perspectives of the academy - Locke, William; Cummings, William K.; Fisher, Donald; SpringerLink (Online service). (Dordrecht New York Springer, 2011)
External drivers are pressing for a more privatized approach to higher education and research, a greater reliance on technology and the more efficient use of resources. But many academics perceive these changes to be imposed from above with little consultation and an inadequate consideration of the beliefs and values that have traditionally guided academic work. The tensions between academic beliefs and contemporary drivers is more evident in certain national systems than in others, and within each system the tension raises particular issues. This book provides a framework for the analysis of recent changes in institutional governance and management in higher education and their impact on the academy and academic work globally. It pinpoints, as far as possible, the areas where recent change is perceived positively and negatively by academics themselves. Changing Governance and Management in Higher Education: The Perspectives of the Academy draws on the findings of an international study based on a common survey of academics in eighteen countries across five continents. The book opens with a chapter outlining the key issues, drivers and challenges that inform contemporary discourse around academic work and the profession in general. It then focuses primarily on national case studies, comparing changes in the top tier with the lower tiers of national systems, public and private institutions, and other differentiating factors as appropriate in each country, which include both mature and emerging higher education systems. The book concludes by proposing a series of generalizations about the contemporary status of governance and management of institutions of higher education
1. Introduction; William K. Cummings, Donald Fisher and William Locke -- Part 1: Emergent higher education systems -- 2. Argentina: Changes in Teachers' Involvement in the Governance and Management of Public Universities; Norberto Fernández Lamarra, Mónica Marquina and Gabriel Rebello -- 3. Brazil: Diverse Experiences in Institutional Governance in the Public and Private Sectors; Elizabeth Balbachevsky and Simon Schwartzman -- 4. Mexico: A Portrait of a Managed Profession; Jesus Galaz Fontes, Juan José Sevilla-García, Laura Elena Padilla-González, José Luis Arcos-Vega, Manuel Gil-Antón and Jorge Martínez-Stack -- 5. Malaysia: Perspectives of University Governance and Management within the Academic Profession; Norzaini Azman, Morshidi Sirat and Mohamad Jantan -- 6. South Africa: Recklessly Incapacitated by a Fifth Column - The Academic Profession Facing Institutional Governance; Charl Wolhuter, Philip Higgs, Leonie Higgs and Isaac Ntshoe -- Part 2: Mature higher education systems -- 7. Australia: The Changing Academic Profession - An encapsulation; Hamish Coates, Ian R. Dobson, Leo Goedegebuure and V. Lynn Meek -- 8. Canada: Perspectives on Governance and Management; Amy Scott Metcalfe, Donald Fisher, Yves Gingras, Glen A. Jones, Kjell Rubenson and Iain Snee -- 9. The United Kingdom: Academic Retreat or Professional Renewal; William Locke and Alice Bennion -- 10. The United States of America: Perspectives on Faculty Governance, 1992-2007; Martin Finkelstein, Ming Ju and William K. Cummings -- 11. Germany: How Changing Governance and Management Affects the Views and Work of the Academic Profession; Ulrich Teichler -- 12. Finland: CAPtive Academics - An Examination of the Binary Divide; Timo Aarrevaara, Ian R. Dobson and Elias Pekkola -- 13. Norway: Between Humboldtian Values and Strategic Management; Agnete Vabø -- 14. Japan: Effects of Changing Governance and Management on the Academic Profession; Akira Arimoto -- 15. South Korea: Decentralized Centralization Fading Shared Governance and Rising Managerialism; Jung Cheol Shin -- 16. Hong Kong: Governance and the Double-Edged Academy; Gerard Postiglione and Wang Shiru -- 17. Comparative Perspectives: Emerging Findings and Further Investigations; William Locke, William K. Cummings and Donald Fisher -- Annex: The Changing Academic Profession Study and Survey
Includes bibliographical references and index
Electronic reproduction.
Keywords: Education, Higher -- Administration; Universities and colleges -- Administration